SDG#3 Sustainable Wellness and #8 Decent Jobs for Honey Business - YEUNG, Shirley Mo Ching (Journal of Ecohumanism, 2025)
Emergence of business usually goes along with the rising green economy with the importance of intangible cultural assest preservation, including wellness in agricultural products of a country and use of advacned technology for replicatign the innovative business models for fullfilling the growing wellness demands of customers. Demand chain and supply chain management of wellness related products, for example, mountain honey/ services of emerged countries under the application of social inclusion, diversity and technological advancement concepts in a society. Educators and industry practitioners need to be aware of these changes to catch up with new skills development and new job creation for sustainable development. In order to understand the new skills development for wellness honey related service industries, this paper is to explore the key elements of Ai in honey business in the past few years through literature search. 9 relevant journal papers related to honey business (2022-2024) and 16 news on new jobs and new skills (2020) have been selected and analyzed with N’vivo software. Based on qualitative and quantitative analysis of these selected literature, three major constructs are found – Ai in Honey Business (1,113 references), Motivation in Honey Wellness Business (1,078), Data Visualizationtion (774 references), Responsive training in wellness (427), Responsive training in ICH, (412), Digital Agriculture (355 references), IoT (323 references). From the perspective of United Nations Sustainable Development Goals (UNSDGs), the results align with the goal# 3 well being for quality of life, goal#4 – quality of education with transferable skills, goal# 8 economic growth with decent job creation and goal#9 innovations for sustainable business. This paper is of practical value in terms of understanding the key elements for sustainable wellness, for example honey wellness business through re-visiting the ways of educating the community on the ways of creating or making use of innovations and ways of measuring improvement in health education for decent jobs. This brings insights to industry practitioners, investors, educators and policy makers on the importance of tracing the trend of emerging industry for sustainable development.